Design and Application of ATS Dispatch Path Search Method - ZHANG Yanqiu; LI Denggen; WANG Min'an; TAO Cui (Kongzhi Yu Xinxi Jishu)
In order to improve the operational capability of automatic train supervision (ATS), reduce the software and hardware cost, a dispatch path search method is proposed to linked devices such as platforms and signals. Based on the station map data and topology theory, the proposed method acquires the connection relationship of the platform in a semi-automatic or fully automatic manner, and the connection data of the platform is stored in the data structure of the adjacent matrix. The path search rule is designed, in which both depth-first search (DFS) and breadth-first search(BFS) are supported to obtain the path group. Automatic or manual methods to meet the project requirements are also proposed. Take the platform as an application case, the method is adapted to train dispatcher and route trigger function related to paths of linked devices. The path group can be reloaded by ATS subsystem, which can improve the ATS performance effectively. The method has been applied to Changsha urban rail transit Line 3 and Line 4, Wuxi urban rail transit Line 4, to support plan editing and train scheduling, and achieves good results, such as the generation time of station map can reduce over 70%,incidental jamming of the route trigger is eliminated when there are more trains,and route files can be generated automatically within minutes (original manual generation took several days).